Evaluation of the radiopacity of rootend filling materials by digitization of radiographic images - Mário Tanomaru Filho; Simone Caetano Laitano; Marcelo Gonçalves; Juliane Maria Guerreiro Tanomaru (Universidade Estadual de Campinas, 2015)
The aim of this study was to evaluate the radiopacity of five root-end filling materials (Sealer 26, Zinc Oxide-Eugenol, Sealapex with zinc oxide, Pro RootTM MTA, and MTA-Angelus). Specimens measuring 10 millimeters in diameter and 1 millimeter in thickness were fabricated and radiographed next to an aluminum stepwedge with variable thickness. Radiographs were digitized and radiopacity values of the materials were compared to those of the aluminum stepwedge. The VIXWIN 2000 software was used to determine the radiopacity in millimeters of aluminum (mm Al). Radiopacity values varied from 2.5 mm Al to 8.9 mm Al. Sealer 26 and ZOE were the most radiopaque (p<0.05), while MTA-based materials presented the least radiopacity; Sealapex with zinc oxide presented intermediate radiopacity. The rootend filling materials presented different radiopacity values; MTAbased materials were the least radiopaque, with radiopacity values next to the minimum recommended.